PKM Pembelajaran Aplikasi Canva di Madrasah Diniyyah Sirojussibyan - Rudi Prasetya; Andri Andri; Julizal Julizal; Halimatussa'diah Halimatussa'diah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Working and studying from home are demands that must be made at this time, since the Covid-19 pandemic due to the Corona virus. Schools were closed, teaching and learning activities were shifted online at home. Because of this demand, many teachers and parents are required to start adapting to remote teaching and learning activities, using technology. Bridging this, many applications are used for learning. Google provides a special website for teaching and learning activities for school students, in the Indonesian version. With this facility, anyone, including teachers, can create internal project hubs, team sites, publicly displayed sites, and more. Everything is done without the help of designers, programmers and IT. This training is for teachers who are still unclear (look confused) how to operate Canva to support distance learning between teachers and students to make it more interesting and fun.